Evaluation of anti-dermatophytic activity of medicinal plants derived products - Gupta, Anu; ., Alisha; Kaur, Sandeep; Gill, Prabhjot Kaur (International Journal of Research in Dermatology, 2020)
Background: Dermatophytes are a group of closely related fungi which are able to invade the keratinized tissue skin, hair and nail. In this study different medicinal plants like Melaleuca alternifolia, Zingiber officinale, Allium sativum, Azadirachta indica, Citrus limonum, Curcuma longa, Cocos nucifera were used as antifungal agent against different dermatophyte species. Methods: A hospital-based study consisting of 320 patients clinically diagnosed having dermatophytic infection who reported to the Dermatology outpatient department (OPD), Adesh medical college, Bathinda was conducted for the period of 2 years. Socio-demographic and clinical information was collected and sample was taken from the edge of infected area which was then collected in 2 ml of Eppendorf. Extracts of medicinal plants were then explored against dermatophyte. The data was evaluated using appropriate statistical method. Results: All dermatophyte species were found sensitive for Melaleuca alternifolia, Zingiber officinale and Allium sativum. These medicinal plants showed very good results as antifungal against dermatophytes while Azadirachta indica and Citrus limonum were moderate sensitive and Curcuma longa and Cocos nucifera did not show any zone of inhibition around the well. Conclusions: This research provides a scientific validation for the use of these medicinal plants in the treatment of dermatophytic infection and could be used in future for dermatophytic infection and other skin infection.